2007
DOI: 10.1038/sj.mp.4002052
|View full text |Cite
|
Sign up to set email alerts
|

Evidence implicating the candidate schizophrenia/bipolar disorder susceptibility gene G72 in mitochondrial function

Abstract: G72 is a strong candidate susceptibility gene for schizophrenia and bipolar disorder, whose function remains enigmatic. Here we show that one splicing isoform of the gene (LG72 ) encodes for a mitochondrial protein. We also provide convergent lines of evidence that increase of endogenous or exogenous G72 levels promotes robust mitochondrial fragmentation in mammalian cell lines and primary neurons, which proceeds in a manner that does not depend on induction of apoptosis or alteration in mitochondrial transmem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
121
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(130 citation statements)
references
References 44 publications
8
121
1
Order By: Relevance
“…G72 gene in schizophrenia and BPAD D-M Otte et al localization signal at the N terminus and is located in the mitochondria (Kvajo et al, 2008). This is supported by our results showing a mitochondrial localization of LG72 upon expression in mouse neuroblastoma cells.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…G72 gene in schizophrenia and BPAD D-M Otte et al localization signal at the N terminus and is located in the mitochondria (Kvajo et al, 2008). This is supported by our results showing a mitochondrial localization of LG72 upon expression in mouse neuroblastoma cells.…”
Section: Discussionsupporting
confidence: 79%
“…Given the mitochondrial localization of heterologously expressed LG72 in human (Kvajo et al, 2008) and mouse cells (Supplementary Figure S1A), these findings suggested the possibility that LG72 affected mitochondrial function and lead to an increased production of ROS. We therefore investigated mitochondrial density and expression of mitochondrial marker enzymes in G72Tg mice.…”
Section: Mitochondrial Dysfunction and Altered Redox State In G72tg Micementioning
confidence: 99%
See 2 more Smart Citations
“…There have been no studies to date examining morphological or morphometric abnormalities in BPD or MDD lymphocytes. Interestingly, two strong schizophrenia candidate genes, Disrupted in Schizophrenia 1 (DISC1) and G72, have splicing isoforms that are targeted to mitochondria although the exact functions of these proteins in the mitochondria remain unknown (41,42).…”
Section: Ultrastructure Studies Of Mitochondrial Abnormalities In Psymentioning
confidence: 99%